Ecophysiological basis of wood formation in ponderosa pine: Linking water flux patterns with wood microdensity variables - Martinez Meier, Alejandro Gabriel (2015)
Climate and stands management have an effect on the process of wood formation via resource availability. To improve knowledge of wood quantity and physical structure, increment cores of ponderosa pine were taken in high- and low-density stands growing in Patagonia, Argentina. Microdensity profiles were performed on trees for which sapflow density (Qs) data were available over two consecutive years (2004 and 2005, dry and wet years, respectively). Conventional and non-conventional microdensity variables were analyzed in the segment of the microdensity profile where Qs was measured. Trees in the low-density stand showed a greater capacity for water transport than trees in the high-density stand, even if no constraints in the soil water availability were confirmed, as was the case for the wet year. Minimum and earlywood density were significantly higher in the high-density stand in several analyzed years. These differences were not reflected in mean density of the whole radial profile. The structural changes in physical wood properties in relation to silvicultural treatments appear to affect plant water status, even in the wet growing season: greater wood density in the first part of the tree-ring may contribute to the observed Qs decrease found in the high-density stand. This fact may lead trees to lack the coordinated mechanisms of response to drought observed in more xeric sites. The increase of wood density in the first part of the tree-ring in ponderosa pine could be not conducive to acclimation, exposing trees to an increasing "dilemma" facing drought.